Characterization of the microbiota of commercially traded finfish fillets. (November 2020) - Shehata, Hanan R.; Mitterboeck, T. Fatima; Hanner, Robert
Graphical abstract: Highlights: Pseudomonas, Photobacterium, and Psychrobacter were most abundant across samples. Alpha diversity differed between fish species and based on label accuracy. Putative spoilage or pathogenic organisms were identified in some fish samples. Abstract: The profile of human gut microbiota is known to be affected by diet and is linked to human health. Seafood is a highly consumed food and it accounts for a large proportion of food-borne illness. The objective of this study is to characterise the microbiota of fish fillets of various species sold in the Canadian market. We test 19 fish fillet samples from nine species in five fish families, ten of which were previously determined to be mislabeled as different species. The microbiota profiles were characterized using 16S rRNA gene high-throughput sequencing. Despite the complexities of the supply chain to produce these fillets, the major microbial groups were fairly consistent across samples. Significant differences in microbial taxa were observed between species, families, and based on labelling accuracy. Several putative spoilage and putative pathogenic taxa were identified. Studying food-associated microbiota can provide comprehensive information on food safety, authenticity, and traceability.